2016
DOI: 10.1039/c6ra11742b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of p-aminohippuric acid with β-cyclodextrin sensitized fluorescence spectrometry

Abstract: Sensitive spectrofluorometric and HPLC with fluorescence detection methods have been developed for detection and determination of para-aminohippuric acid (a marker used for estimating effective renal plasma flow) in the presence of β-cyclodextrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Several reports have suggested the formation of 1:2 host–guest inclusion complexes with β‐CD [37–39]. Thus, hydrophobic methylated β‐CD moieties can form a relatively stable complex with phenyl groups on the surface of the stationary phase in a phenyl column to permit the column to act as a permanent methylated β‐CD‐coated chiral column.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have suggested the formation of 1:2 host–guest inclusion complexes with β‐CD [37–39]. Thus, hydrophobic methylated β‐CD moieties can form a relatively stable complex with phenyl groups on the surface of the stationary phase in a phenyl column to permit the column to act as a permanent methylated β‐CD‐coated chiral column.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the excimer fluorescence was attributed to formation of the 1:2 β‐CD‐drug inclusion complex. Alremeithi et al determined p ‐aminohippuric acid with β‐CD by sensitized fluorescence spectrometry 34 . The 1:2 host‐guest inclusion between β‐CD and p ‐aminohippuric acid became evident by mass spectrometry and density functional theory calculations that supported the formation of an excimer state at 355 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, HP‐β‐CD may form a complex with phenyl groups on the surface of the stationary phase in the column to allow a phenyl column to act as a transient chiral column. When mandelic acid was injected in the phenyl column, the ternary complex could be formed by aggregation of a phenyl group on the stationary phase, HP‐β‐CD, and a phenyl group of mandelic acid as the β‐CD inclusion complexes with two guest molecules having a phenyl group were reported 34,35 . The longer retention time for D‐mandelic acid in the chromatographic process suggests that the ternary inclusion complex with D‐mandelic acid was more stable than that with L‐mandelic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of an inclusion complex between host and guest moieties significantly alters the solubility , and spectral properties , of the hydrophobic guest molecules. Considerable attention has been paid on the use of CDs as a means of improving aqueous solubility and spectrofluorometric methods for the identification of various analytes .…”
Section: Introductionmentioning
confidence: 99%